Intraoperative Ultrasound: Emerging Technology and Novel Applications in Brain Tumor Surgery - Giammalva, Giuseppe Roberto; Ferini, Gianluca; Musso, Sofia; Salvaggio, Giuseppe; Pino, Maria Angela; Gerardi, Rosa Maria; Brunasso, Lara; Costanzo, Roberta; Paolini, Federica; Di Bonaventura, Rina; Umana, Giuseppe Emmanuele; Graziano, Francesca; et al. (Frontiers in Oncology, 2022)
Intraoperative ultrasound (IOUS) is becoming progressively more common during brain tumor surgery. We present data from our case series of brain tumor surgery performed with the aid of IOUS in order to identify IOUS advantages and crucial aspects that may improve the management of neurosurgical procedures for brain tumors. From January 2021 to September 2021, 17 patients with different brain tumors underwent brain tumor surgery aided by the use of IOUS. During surgery, the procedure was supported by the use of multiples ultrasonographic modalities in addition to standard B-mode: Doppler, Color-Doppler, elastosonography and Contrast-Enhanced Intraoperative Ultrasound (CEUS). In selected cases, the use of IOUS during surgical procedure was combined with neuronavigation and the use of intraoperative fluorescence by the use of 5-ALA. In 1 patient, a preoperative ultrasound evaluation was performed through a former iatrogenic skull defect. This study confirms the role of IOUS in maximizing the EOR, which is strictly associated with postoperative outcome, overall survival (OS) and patient’s quality of life (QoL). The combination of ultrasound advanced techniques such as Doppler, Color-Doppler, elastosonography and Contrast-Enhanced Intraoperative Ultrasound (CEUS) is crucial to improve surgical effectiveness and patient’s safety, while expanding surgeon’s view.